CINESONIC REALITY IN ART AND DESIGN ON DIGITAL MEDIA - Setiyawan, Clemens Felix; Murwaningrum, Dyah (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Digital technology has significantly transformed the concepts and practices of art, including the creation of art and design. Cinesonic emerged as an innovative form that integrates the visual and the aural into a unified and holistic aesthetic through multisensory experiences. Consequently, it has fostered extensive artistic expression, depth and diversity of meaning, and the emergence of new paradigms in contemporary culture. This study aims to describe cinesonic as a medium for the recreation of art and culture while simultaneously fostering visual-aural awareness in everyday human activities, which are often overlooked. The development of visual-aural awareness has the potential to enhance the depth and quality of audience appreciation. This research is qualitative, employing a descriptive-analytical method. A historical explanation approach is utilized to guide the description within spatial and temporal boundaries. Data were collected from prior papers and works discussing the cinesonic movement and its realities in art and design. The paper focuses on examining the definition, history, and application of the cinesonic concept across various contexts. The findings reveal that cinesonic expands the boundaries of traditional aesthetics, offers sharp social critique, and creates multisensory interactions that are highly relevant to the digital era. At an advanced stage, cinesonic is anticipated to become an art form capable of enhancing artistic experiences, fostering awareness, and shaping new insights into the relationships between humans, technology, and their environments.